Xuebijing Injection Alleviates the Inflammatory Response in Patients with Venous-Arterial Extracorporeal Membrane Oxygenation: A Prospective Randomized Controlled Study - Zhiyong Yuan; Ying Liu; Fuhua Wang; Xiaoning Han; Zhenhui Dong; Jinyan Xing; Xiaotian Chang (Reviews in Cardiovascular Medicine)
Background: Both acute myocardial infarction (AMI) and its salvage treatment, venoarterial-extracorporeal membrane oxygenation (VA-ECMO), may lead to the production of proinflammatory cytokines and further aggravate tissue damage. Xuebijing (XBJ) may modulate cytokine production involved in the inflammatory response. We aimed to determine the efficacy of XBJ in cardiogenic shock patients on VA-ECMO. Methods: This was a prospective, randomized trial carried out in an intensive care unit of a tertiary teaching hospital. Patients with cardiogenic shock after acute myocardial infarction undergoing percutaneous coronary intervention (PCI) with VA-ECMO support were randomly divided into a Xuebijing group and a control group. Cytokines, inflammatory factors and left ventricular ejection fraction (LVEF) were compared between the groups. Results: 41 patients were enrolled in the study, with 21 in the Xuebijing group and 20 in the control group. 28 (68.3%) were male, and the average age was 64.71 ± 8.18 years old. There was no difference in APACHEII (acute physiology and chronic health evaluation II) score, LVEF, or cytokine and inflammatory factors collected before extracorporeal membrane oxygenation (ECMO) between the two groups. The levels of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) in the Xuebijing group were lower than those in the control group in the first 24 hours, 48 hours and 72 hours after ECMO (p < 0.05). The LVEF in the Xuebijing group was higher than that of the control group at 48 hours (31.57 ± 3.43 vs. 28.35 ± 4.42, p = 0.013). This trend persisted at 72 hours. The duration of ECMO support in the Xuebijing group was 5.57 ± 2.11 days, which was shorter than that in the control group (p = 0.033). Conclusions: Xuebijing injection can reduce the inflammatory response and improve cardiac function in patients with acute myocardial infarction treated with VA-ECMO to a certain extent. Clinical Trial Registration: Chinese Clinical Trial Registry (ChiCTR), ChiCTR2100054069, Registered 8, December 2021, https://www.chictr.org.cn/showproj.html?proj=142869.